„Nu e cazul să ne dăm ceea ce nu suntem”. Spre o înţelegere a comunismului prin Bandiţii de Vasile Ernu: “It’s not the case to pretend to be something we are not”. Towards an understanding of communism through The Bandits by Vasile Ernu - Stoichiţ, Iulia (Swedish Journal of Romanian Studies, 2021)
“The Bandits”, Vasile Ernu’s second volume of his trilogy, the trilogy of marginal men, describes the world of thieves, of bandits, of criminality in a communist society, without the narrator ever becoming one of them. He is more of an adopted son, someone who has almost unmediated access to this world without suffering the repercussions of revealing that world’s secrets. This should not to be understood that he has total access to the bandits’ secrets, but that he is not viewed as a threat, even if he reveals more of this world than others. The narrator is accepted because he does his best to be himself and this is a value of utmost importance for this marginal group of people, others knowing and owning their identity, the type of narrative they tell about themselves. On the other hand, the narrator is himself a marginal man as well, considering the fact that he grew up among religious people who were quite fundamentalists in their way of expressing this belief (but not in the way in which we picture today religious fundamentalism: bombing, Muslims, terror). Thus, this essay is meant as a study of one’s sense of identity when having to juggle with more identities, when having to evade (or even be subversive towards) the more pervasive, totalitarian regime in which these marginal men find themselves.